Влияние однородности шлифпорошков сверхтвердых материалов на работоспособность инструмента - Зайцева, И.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
In article it is shown, that increase of uniformity of superhard materials (SHM) is achieved by carrying out of sorting powders in the surface imperfection and additional division of grains of SNM representing a number of a geometrical progression of the twentieth (R-20) of some numbers. The increase of the efficiency of tools with SHM powders of higher uniformity is shown. The serviceability of SHM powders with high uniformity is much above in comparison with initial powder.